Permeability of muddy clay and settlement simulation. (1st August 2015) - Zhang, Minxi; Zhu, Xiwen; Yu, Guoliang; Yan, Jianming; Wang, Xianben; Chen, Menglin; Wang, Weiming
Abstract: In this study, the permeability characteristics of hydraulic-filled mud from Yueqing port and natural clays from the Minghang River, China, were investigated in a laboratory. The obtained experimental results, when combined with other researchers׳ experimental data, indicate that the void ratio and clay content are two major factors influencing the permeability of muddy clays. The variation of the permeability with the void ratio is best represented by a linear e vs. lg k relationship. Furthermore, the permeability decreases as the clay content increases. Then, a new empirical formula of the form lg k=A ( P ) e+B ( P ) is proposed to calculate the permeability of fine-grained muddy clays with the clay content P as a parameter. By using this formula and Gibson׳s equation, the complete settling process of a reclamation foundation that has been newly filled with dredged mud is simulated. The simulation results show that the variation of the void ratio and temporal settlement amount are in line with the measured field data. Highlights: The void ratio and clay content are two major factors influencing the permeability. The permeability decreases as the clay content increases. A new e–lg k relationship is proposed as a function of clay content. The proposed formula is successfully used in muddy clay settlement prediction.